Hierarchical graphene/SiC nanowire networks in polymer-derived ceramics with enhanced electromagnetic wave absorbing capability. Issue 11 (September 2016) - Han, Meikang; Yin, Xiaowei; Duan, Wenyan; Ren, Sa; Zhang, Litong; Cheng, Laifei
Abstract: A high-performance electromagnetic wave absorbing composite based on graphene and polysiloxane-derived SiOC ceramic is realized via the polymer pyrolysis process. Hierarchical architecture consisting of two-dimensional graphene and one-dimensional SiC nanowire in ceramic matrix is achieved owing to the heterogeneous nucleation of SiC nanowires promoted by graphene at lower temperature. The dielectric and microwave absorption properties of the composites were studied at 293–673 K. When graphene oxide loading is 3 wt%, the composite attains a minimum reflection loss value of −69.3 dB at 10.55 GHz with a thickness of 2.35 mm. With the increase of temperature, the composite exhibits better absorbing performance that the effective absorption bandwidth reaches 3.9 GHz at 673 K. The hierarchical networks with graphene/SiC nanowires achieved in SiOC matrix provide a feasible process for the realization of efficient electromagnetic wave absorption in ceramic-based composites at high temperature.